A study on International Safety Management (ISM) at Alam Maritim (M) Sdn. Bhd. / Nik Nur Amalina Nik Ab Rahman - Nik Ab Rahman, Nik Nur Amalina (Faculty of Business and Management, 2009)
This case study exploring the International Safety Management (ISM) that implement by Alam Maritim (M) Sdn Bhd (AMSB) and the theories. Safety management objectives of the Company should provide the safe practices in ship operation and a safe working environment. Another objective of the safety management of the Company is to establish safeguards against all identified risk. Next, the Company should continuously improve safety management skill management skill of personal ashore and abroad ship including preparing for emergencies related both to safety and environmental protection. The main issue of this study is to explore the extent of the security measures taken by AMSB in order to prevent further accident and incident from happening in the future. This issue deeply explained in the report in order to be more clarifying for understanding of safety management. Some of the suggestions have been explained in enhancing the safety management that are practiced in AMSB.